Going Global through Social Sciences and Humanities: A Systems and ICT Perspective Proceedings of the 2nd International Conference "Going Global through Social Sciences and Humanities", 27-28 February 2019, Tomsk, Russia - Anikina, Zhanna; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2019)
This book presents contributions submitted to the 2nd international conference Going Global through Social Sciences and Humanities (GGSSH 2019) held in Tomsk, Russia on 27-28 February 2019. The conference focused on such issues as interdisciplinary pedagogy, language teaching and learning, cultural studies and linguistics, particularly highlighting global academic integration and professional development for research. As such, the event provided a platform for discussions and sharing publication activities, to help Russian academics to take first steps toward global research. Showcasing the ongoing Russian research in focus areas, this book is of interest to a diverse academic audience working in social sciences and humanities, particularly those from the post-Soviet countries.
Training a Pre-Service Foreign Language Teacher Within the Linguo-Informational Educational Environment -- Peculiarities of Psychological Culture Development For Gifted Senior Pupils in Rural Settings Developing Professional Competences with Interactive Teaching Methods at Tertiary Education -- Providing Professional Self-Realization for Technical University Students when Teaching the Humanities -- Peculiarities of Psychological Culture Development For Gifted Senior Pupils in Rural Settings -- Intellectics Fundamentals in a Professional Activity of a Future Bachelor -- Nomadic School: Problem of Access to Quality Education -- Peculiarities of Leadership Potential Development in Educational Environment -- Regional Aspects in a New Engineering Way of Thinking Development of Bachelors of Techniques and Technology -- Conditions Affecting the Professional and Project Training of Engineering Personnel -- An English Language Textbook: A Friend Or A Foe -- Combinatorial Linguodidactics as a New Direction in the Methodology of Foreign Language Teaching -- Self-instructed Distance e-Learning of Foreign Languages in the Far North of the Russian Federation -- Research on Teacher Career Motivation in the Russian Pedagogical University Context.
Keywords: Computational intelligence; Sociology -- Methodology; Computational Intelligence; Sociological Methods